2009
DOI: 10.1089/end.2008.0073
|View full text |Cite
|
Sign up to set email alerts
|

Transgastric NOTES: Current Experience and Potential Implications for Urologic Applications

Abstract: Natural orifice translumenal endoscopic surgery (NOTES) in its current form uses flexible endoscopy technology to perform surgical procedures in the abdomen. NOTES is emerging as a potential alternative to both open and laparoscopic surgery, and the technique eliminates the requirement of abdominal incisions. To date, multiple intraperitoneal procedures have been reported in animal models while only a few reports of NOTES performed in humans exist. Several potential advantages of NOTES include the elimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Thus far, NOTES has been successfully completed experimentally via transgastric [15], transvaginal [16], transcolonic [17], and transvesical [18] routes (Table 1). Kalloo et al demonstrated the feasibility of transgastric access to the peritoneal cavity in a porcine model [5].…”
Section: Natural Orifice Transluminal Endoscopic Surgery: Access and mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, NOTES has been successfully completed experimentally via transgastric [15], transvaginal [16], transcolonic [17], and transvesical [18] routes (Table 1). Kalloo et al demonstrated the feasibility of transgastric access to the peritoneal cavity in a porcine model [5].…”
Section: Natural Orifice Transluminal Endoscopic Surgery: Access and mentioning
confidence: 99%
“…Thus, the ideal telescope for LESS should remove the light cord and camera head from the operative field. Low-profile camera systems have been introduced for this purpose [15,[30][31][32].…”
Section: Opticsmentioning
confidence: 99%
“…Without reliable gastric closure, clinicians remain concerned about postoperative leakage, fistula formation, intraperitoneal contamination, and infection. In addition, the use of the flexible endoscopic platform, as well as problems relating to specimen retrieval, have limited the application of transgastric NOTES [11]. Recently, the transvaginal approach received attention.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable endoscopic gastric closure technique must be developed and improved. 19 As all other cavities were explored, the first conclusion we made was that lower abdominal ports might be better for upper abdominal procedures and useful as an accessory port for transgastric access.…”
Section: Commentmentioning
confidence: 99%